A Review Of Hundred Years Of Wheat Research And Development In Punjab (1911-2010) - L. H. Akhtar (Pakistan Journal of Science, 2010)
This paper presents share of agriculture to GDP and workforce and its growth rate. Importance of wheat as food, its contribution towards value added and GDP has been reviewed. Food requirements of Pakistan have been discussed. Area, production and yield per ha during 2006-07 and 2007-08 have been given. Wheat situation in 2009, uses, availability and consumption of wheat has been presented. Support price and quality seed distribution has been discussed. A review of hundred years of wheat research and development in Punjab from 1911 to 2010 and the wheat varieties developed have been tabulated with their name, pedigree and year of release. Constraints being faced by agriculture research and their solutions have been suggested.